IRON DEFICIENCY AND IRON DEFICIENCY ANEMIA - A GLOBAL PUBLIC HEALTH PROBLEM - Laura Florescu; Oana-Raluca Temneanu; Nicolai Nistor; Dana Elena Mindru (Amaltea Medical Publishing House, 2016)
Iron deficiency is defined as a condition in which there is not an adequate iron level necessary to maintain the normal physiologic functions. Having the magnitude of epidemics, anemia is a global public health problem, which affects both the emerging countries and the developed ones, with major consequences for human health and for social and economic development. Nowadays, iron deficiency and especially iron-deficiency anemia, remains one of the most severe and important nutritional deficiencies. Each group of age is vulnerable. Infants, small children, pre-school children and teenagers show a higher risk of iron deficiency. Accordingly, the World Health Organization developed an ample package of public health measures that approaches all the aspects related to iron deficiency and iron-deficiency anemia. Trying to diminish the prevalence of iron deficiency and iron deficiency anemia, the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) has synthesized in 2014 the recommendations used also at present for martial prophylaxis.